2017
DOI: 10.1016/j.rmed.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The variability of respiratory symptoms and associated factors in COPD

Abstract: Few studies have investigated the variability of COPD-related symptoms or factors related to symptom variability. This observational, prospective, multicentre study was conducted to describe the number and intensity of morning and night-time respiratory symptoms and their variability over one week using the Night-time and Early Morning Symptoms of COPD Instruments (NiSCI and EMSCI) to evaluate stable COPD patients. Logistic regression analyses were performed to investigate factors associated with symptom varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
3
23
0
2
Order By: Relevance
“…Cough and sputum, followed by dyspnoea, were also the most frequent morning symptoms in a more recent international study, with 88% of patients reporting these symptoms being of mild or moderate severity [6]. The prevalence of morning symptoms in COPD ranges from 37% to 94% across different studies, depending on the severity of the patients studied and the definition used [4,27,28]. We used a very restrictive definition of "significant" morning symptoms that required at least moderate dyspnoea plus another moderate symptom.…”
Section: Discussionmentioning
confidence: 98%
“…Cough and sputum, followed by dyspnoea, were also the most frequent morning symptoms in a more recent international study, with 88% of patients reporting these symptoms being of mild or moderate severity [6]. The prevalence of morning symptoms in COPD ranges from 37% to 94% across different studies, depending on the severity of the patients studied and the definition used [4,27,28]. We used a very restrictive definition of "significant" morning symptoms that required at least moderate dyspnoea plus another moderate symptom.…”
Section: Discussionmentioning
confidence: 98%
“…,16,23,[28][29][30][32][33][34] For example, a prevalence of 81.4% for morning symptoms and 63.0% for night-time symptoms was reported by Miravitlles et al4 Similar trends of morning and/or daytime versus night-time symptom prevalence were reported by Bateman et al23 (94.4 versus 88.3%), Marth et al28 (91.7 versus 70.6%), Soler-Cataluna et al…”
mentioning
confidence: 53%
“…Interestingly, in the two articles assessing the relationship between symptoms and a history of exacerbations (all based on large-scale, observational/ real-world datasets), the presence of morning or daytime COPD symptoms was strongly associated with a higher frequency of exacerbations in the preceding 12 months. 14,15 Another study by Miravitlles et al 33 found that any type of symptom variability was significantly associated with more exacerbations in the previous year.…”
Section: Trial Characteristics and Participantsmentioning
confidence: 98%
See 2 more Smart Citations